Information technology strategies how leading firms use IT to gain an advantage - Rapp, William V. (Oxford University Press, 2011)
The focus of this book is on educating on the strategic principles fundamental to using information technology to gain market control. It provides case examples of how to use IT to enhance existing core competencies and strategies. The book is designed to help managers struggling with how to advantageously harness the new information revolution. It can also support executive and business education programs on managing technology when few such studies exist. While Internet and information technologies are currently hot topics, many firms and executives are without the tools and knowledge of how to actually use them to improve results. This book describes how major non-information technology companies are doing this and the strategic principles employed.